Examining the Beliefs of Skilled Nursing Facility Directors of Nursing Regarding BSN Completion and the Impact of Nurse Leader Education on Patient Outcomes. (February 2019) - Holle, Cynthia L.; Sundean, Lisa J.; Dellefield, Mary Ellen; Wong, John; Lopez, Ruth Palan
Abstract : Research suggests that acute care patients cared for by baccalaureate-educated nurses have better outcomes. Directors of nursing (DONs) in skilled nursing facilities (SNFs) have lower rates of baccalaureate attainment than acute care nurses for unclear reasons. To understand the interest in advancing education, researchers surveyed SNF DONs in Connecticut to examine their beliefs about academic advancement and the impact of DON education on resident outcomes. Nearly 70% of participants with diplomas and associate degrees lacked interest in degree advancement and did not believe a baccalaureate degree is necessary for DONs or that DON level of education impacts resident outcomes. Alternatives to degree completion may include interventions to provide SNF DONs with skills for improving resident outcomes. Abstract : Supplemental digital content is available in the text.